Aeromedical retrieval for suspected appendicitis in rural and remote paediatric patients. Issue 1 (20th February 2020) - Harwood, Abby; Black, Sarah; Sharma, Pritish; Bishop, Lara; Gardiner, Fergus W.
Abstract: Introduction: The aim of this paper was to describe the characteristics of paediatric patients who underwent an aeromedical retrieval within Australia (gender and Indigenous status) for suspected appendicitis between 1 July 2014 and 30 June 2018 (4 years). By understanding these trends, we hope to further justify the need for point‐of‐care ultrasound training for clinicians working in rural and remote Australia. Method: Participants included Royal Flying Doctor Service (RFDS) patients aged 0–18 years (inclusive) who underwent an aeromedical retrieval for suspected appendicitis within Australia. Data were collected and coded on each patient's inflight working diagnosis, using the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification (ICD‐10‐AM) coding method. A combination of descriptive statistics and chi‐square analyses was used in data analysis, with significance considered at <0.05. Results: There were 384 children with a working diagnosis of suspected appendicitis, including 191 (49.7%) males and 193 (50.3%) females, with 133 (34.6%) patients identifying as Aboriginal and/or Torres Strait Islander (hereafter referred to as Indigenous) Australians. The aeromedical retrievals were from rural and remote locations to inner‐regional or metropolitan hospitals, with an average distance flown of 339.0 (SD = 206.4) kilometres. The RFDS most frequently retrieved for acute appendicitis (n = 159; 41.4%), acute abdominal pain (n = 127; 33.1%), and unspecified appendicitis (n = 84; 21.9%). There were non‐significant (P = 0.9) diagnostic differences between genders. Non‐Indigenous patients were overrepresented, compared with Indigenous patients, in relation to a transfer with a diagnosis of acute appendicitis (P = <0.01), whereas Indigenous patients were overrepresented, compared with non‐Indigenous patients, in relation to transfers with diagnoses of acute abdomen pain and unspecified appendicitis (P = <0.01). Conclusion: A significant number of paediatric patients are aeromedically retrieved from rural and remote locations with a diagnosis of appendicitis or acute abdominal pain. Future research should consider whether training in abdominal point‐of‐care ultrasound reduces retrievals.